Some questions of improvement of a tax system of Azerbaijan - Maharramov, R.B.; Mamedzade, N.R.; Madatova , Sh.Q. (BUKETOV BUSINESS REVIEW, 2019)
At the present stage of development of Azerbaijan a stable tax system is one of the most significant mechanisms affecting the functioning of the country’s economy. The importance of developing a system of taxes and fees is indisputable. The efficient functioning of the entire state depends on how well the tax system is built, how well it is thought out. This is especially true for any state, since taxes form more than 50 % of the country’s budget. Taxes and fees play a fiscal and regulatory role, and in this regard, it becomes important to continuously implement comprehensive measures aimed at eliminating deficiencies and improving the current tax system. The article discusses some issues of improving the tax system, the changes in the Tax Code of Azerbaijan, included in the budget package of 2019, some innovations in tax legislation, in particular, provided benefits for micro, small and medium businesses, issues related to taxation of incomes of employees of The private sector, which does not operate in the areas of oil and gas, the attention is paid to regulation of the ratio of payments for state social insurance between employee and employer. The issues of providing benefits to micro, small and medium-sized enterprises on income tax, income tax and VAT are also discussed. According to the authors of the article the implemented systemic reform will reduce the tax burden on compulsory social insurance contributions and reduce informal employment.